Spatial Differentiation Characteristics and Driving Mechanism of Rural Settlements Transformation in the Metropolis: A Case Study of Pudong District, Shanghai - Li, Kaiming; Geng, Huizhi; Yue, Liying; Li, Kaishun; Huang, Lei (Frontiers in Environmental Science, 2021)
Under rapid urbanization, rural China has undergone a drastic transformation, especially in the metropolis. Revealing the evolution laws of rural settlements is critical for effectively providing references. Although many previous studies demonstrated the transformation laws of rural settlements from multiple scales, few focused on the spatial differentiation within the metropolis. This study constructs the spatial conversion intensity index, conversion structure significance index, and landscape metrics to investigate the spatial differentiation characteristics, classify the transformation patterns, and reveal driving mechanisms of rural settlements in Pudong district at the township level. The results demonstrated a significant decrease in settlements' size, and the values decreased from urban-rural fringe to exurban area. The conversion structure of settlements varied within urban-fringe, suburban, and exurban areas. The settlements' morphology became more regular and compact, but to a varying degree. Based on these findings, three transformation patterns of rural settlements were summarized: the rapid disappearance pattern, the physical decay pattern, and the orderly transformation pattern. Further analysis indicated that they were mainly caused by urban encroachment, limitation of geographic conditions, and planning policies separately. These conclusions reveal the spatial differentiation characteristics of rural settlements in the metropolis of developing countries and provide scientific guidance for sustainable rural development.